A carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material and its preparation method and application
By growing the copper oxide buffer layer on the surface of the carbon cloth and growing cobalt hydroxide and alkaline copper carbonate nanostructures on its surface by hydrothermal method, forming a multi-dimensional hybrid structure composite material, the problem of short cycle life of the supercapacitor is solved, and high specific capacitance and excellent cycle stability are achieved.
Patent Information
- Application Number
- CN202211697202.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-28
AI Technical Summary
The prior art is difficult to extend the cycle life of supercapacitors without sacrificing power density and energy density, especially when using electroactive materials, where the use of adhesives results in loss of active sites.
The composite material with a multi-dimensional hybrid structure is formed by growing a cuprous oxide buffer layer on the surface of the carbon cloth and simultaneously growing two-dimensional cobalt hydroxide nanosheets and three-dimensional basic copper carbonate nanoblocks on its surface by hydrothermal method.
The composite material significantly improves electrochemical performance, including the lowest charge transfer resistance and the highest cycling stability by significantly increasing the contact area between the electrolyte and the electrode material and shortening the ion and electron transport path.
Smart Images

Figure CN116081701B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material synthesis, and in particular relates to a carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material and a preparation method and application thereof. Background Art
[0002] Faced with the rapid growth of global energy consumption and many other problems such as excessive use of fossil fuels, there is an urgent need to develop a clean and sustainable energy strategy. Among various energy storage devices, supercapacitors (SCs) are the most promising one, which has a series of advantages such as fast charging and discharging speed, high power density, and long cycle life. However, there is still a major challenge in the practical application of supercapacitors, that is, how to further extend the cycle life without sacrificing power density and energy density. Generally speaking, one of the effective strategies to improve energy storage performance is to select battery-type materials with a wider redox potential window as electrode materials for supercapacitors.
[0003] In recent years, transition metal oxides and hydroxides have attracted extensive attention due to their rich oxidation states, large specific surface area, non-toxic, abundant resources, and environmental friendliness. For example, two-dimensional cobalt hydroxide nanosheets have large interlayer spacing, which can provide large specific surface area and efficient ion transport channels. In addition, transition metal basic carbonates have been widely used as battery-type supercapacitor electrode materials due to their large specific surface area, superior energy storage performance, environmental protection, and low cost. Among several transition metal basic carbonates, three-dimensional basic copper carbonate bulk nanomaterials can be used in energy storage devices due to their advantages such as multiple redox states, stable structure, and good wettability. However, as far as we know, there are few reports on combining the above two materials and using them to prepare flexible electronic devices.
[0004] Flexible energy storage devices with high energy density, strong mechanical properties and long life can meet the rapidly growing demand for flexible electronic devices. However, conventional electroactive materials often require the use of adhesives when made into electrodes, which greatly reduces the active sites of the electroactive materials. The present invention proposes a method for growing self-supporting nanostructured electroactive materials on a conductive substrate, which can effectively avoid the use of adhesives to increase the "self-weight" of the electrode to retain the active sites of the electroactive materials. Carbon cloth is widely used as a flexible current collector for loading electroactive materials due to its excellent chemical stability, good conductivity and excellent mechanical strength.
[0005] However, it is difficult for electroactive materials to obtain both stable electrode structure and excellent electrochemical performance on carbon cloth. Directly growing cobalt hydroxide nanostructures on carbon cloth usually forms small and easily stacked sheets, resulting in the loss of active sites. In order to solve this problem, it is necessary to introduce suitable materials between the carbon cloth and the outer nanostructure. It is worth noting that cuprous oxide as a transition metal oxide can not only improve the capacitance, but also act as a buffer layer to protect the substrate, protect the carbon cloth substrate from damage, and provide sufficient buffer space for the volume expansion that may occur in the electrode material during the charge and discharge process, so as to maintain the high specific capacitance and mechanical strength of the electrode material. Summary of the invention
[0006] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to design and provide a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material and its preparation method and application. The composite material of the present invention can be used as a supercapacitor electrode material.
[0007] The present invention is realized by a simple wet chemical oxidation strategy combined with a hydrothermal method. After the hydrothermal reaction, the two-dimensional cobalt hydroxide nanosheets and the three-dimensional basic copper carbonate nanoblocks are grown on the surface of the cuprous oxide buffer layer in no particular order, forming a composite material with a multidimensional hybrid structure. Its unique two-dimensional nanosheet / three-dimensional nanoblock hybrid structure can exert a significant synergistic effect. Specifically, the transmission path of ions and electrons of the two-dimensional cobalt hydroxide nanosheet is shorter, and the charge transfer and ion diffusion rates are faster, while the structure of the three-dimensional basic copper carbonate nanoblock is relatively stable and has a larger cycle stability. Therefore, the hybrid structure of the two-dimensional nanosheet / three-dimensional nanoblock can fully combine the advantages of the two structures, effectively improve the contact area between the electrolyte and the electrode material, shorten the transmission path of ions and electrons, and maintain a higher stability at the same time, which is reflected in the electrochemical AC impedance test. The composite material has the lowest charge transfer resistance, and in the cycle stability test, the composite material has the highest cycle stability, so that the electrode material has excellent electrochemical performance.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] On the one hand, the present invention provides a carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material, which is a multidimensional self-supporting composite material with a hybrid structure of two-dimensional nanosheets and three-dimensional nanoblocks.
[0010] The carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material is prepared by plating a copper layer on the surface of the carbon cloth to form a conductive substrate, covering the surface of the copper layer with a layer of cuprous oxide film by alkali-assisted wet chemical oxidation, introducing cobalt hydroxide, and performing a hydrothermal reaction to obtain the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material.
[0011] In a second aspect, the present invention provides a method for preparing the carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material, comprising the following steps:
[0012] (1) pre-treating the carbon cloth, placing it in a chemical plating solution, and performing chemical copper plating with magnetic stirring, taking out the carbon cloth, washing it with ultrapure water, and drying it to obtain a carbon cloth@copper conductive substrate;
[0013] (2) weighing sodium hydroxide and ammonium persulfate and dissolving them in ultrapure water, ultrasonicating until the solution is clear and transparent, immersing the carbon cloth @ copper conductive substrate in the solution, performing in-situ etching and oxidation, taking out the carbon cloth, repeatedly rinsing it with ultrapure water, and calcining it in a muffle furnace to obtain a carbon cloth @ copper / cuprous oxide precursor;
[0014] (3) Weighing cobalt nitrate hexahydrate and urea and dissolving them in ultrapure water, ultrasonicating until the solution becomes clear and transparent, transferring the solution into a high-pressure reactor, placing a carbon cloth@copper / cuprous oxide precursor, performing a hydrothermal reaction, repeatedly washing with ultrapure water, and drying to obtain a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material.
[0015] The preparation method, the reaction conditions of the chemical copper plating are: temperature 30-40°C, preferably temperature 35°C, time 90-180min, preferably time 150min;
[0016] The drying conditions are: temperature 50-100°C, time 5-9h;
[0017] The mass and volume ratio of the sodium hydroxide, ammonium persulfate and ultrapure water is 3-6 g: 0.5-1.5 g: 30-60 mL;
[0018] The in-situ etching and oxidation conditions are: temperature 30-40°C, preferably 35°C, time 10-20 min, preferably 15 min;
[0019] The calcination conditions are: temperature 180-200° C., time 3-4 hours.
[0020] In the preparation method, in step (3), the mass ratio of cobalt nitrate hexahydrate to urea is 1-2:2-3;
[0021] The conditions of the hydrothermal reaction are: temperature 120-140°C, preferably 120°C, time 10-12h, preferably 12h;
[0022] The drying conditions are: temperature 50-100° C., time 10-12 h.
[0023] In the preparation method, the specific steps of pre-treating the carbon cloth are:
[0024] (A) The carbon cloth is cleaned with ultrapure water, anhydrous ethanol, and ultrapure water ultrasonically in sequence, and dried for later use;
[0025] (B) Mixing concentrated nitric acid and concentrated sulfuric acid as a mixed acid solution, placing the dried carbon cloth in the mixed acid solution and subjecting it to magnetic stirring for acidification, taking out the carbon cloth, and ultrasonically cleaning it with ultrapure water, anhydrous ethanol, and ultrapure water in sequence, and drying it for later use;
[0026] (C) weighing stannous chloride dihydrate and dissolving it in dilute hydrochloric acid as a sensitizing solution, placing the dried carbon obtained in the above step (B) in the sensitizing solution and magnetically stirring for sensitization treatment, taking out the carbon cloth, repeatedly washing it with ultrapure water, and drying it for later use; (D) weighing silver nitrate and dissolving it in dilute ammonia water as an activation solution, placing the carbon obtained in the above step (C) in the activation solution and magnetically stirring for activation treatment, taking out the carbon cloth, repeatedly washing it with ultrapure water, and drying it to obtain a pre-treated carbon cloth;
[0027] The preparation method of the chemical plating solution is:
[0028] (a) Weigh copper sulfate pentahydrate and dissolve it in ultrapure water, and sonicate until the solution becomes clear and transparent to form solution A;
[0029] (b) Weighing potassium sodium tartrate, sodium hydroxide and sodium carbonate, dissolving them in ultrapure water, and sonicating until the solution becomes clear and transparent to prepare solution B;
[0030] (c) Solution A and solution B are mixed, formaldehyde is added, and the pH is adjusted to 12 to obtain a chemical plating solution.
[0031] The preparation method is characterized in that the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 10:20;
[0032] The mass and volume ratio of the stannous chloride dihydrate to the dilute hydrochloric acid is 0.2-0.4 g:10-14 mL, and the concentration of the dilute hydrochloric acid is 1.2 M;
[0033] The mass-to-volume ratio of the silver nitrate to the dilute ammonia water is 0.05-0.1 g:10-14 mL, and the concentration of the dilute ammonia water is 0.134 M;
[0034] The reaction time of the acidification treatment is 8 to 12 hours, preferably 10 hours;
[0035] The reaction time of the sensitization treatment is 20 to 30 minutes, preferably 25 minutes.
[0036] The reaction time of the activation treatment is 10 to 20 minutes, preferably 15 minutes.
[0037] The drying conditions are: temperature 50-100°C, time 5-9h;
[0038] In the preparation method, the mass ratio of copper sulfate pentahydrate, potassium sodium tartrate, sodium hydroxide and sodium carbonate is 0.5-1.5:2-5:0.4-1:0.2-0.5;
[0039] The volume ratio of the formaldehyde, A solution and B solution is 2-6:22-34:36-60.
[0040] In a third aspect, the present invention provides the use of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material as a supercapacitor electrode material.
[0041] In a fourth aspect, the present invention provides a working electrode in an electrochemical three-electrode system, characterized in that it comprises the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] 1. The present invention utilizes the characteristics of carbon cloth with excellent chemical stability, good electrical conductivity and excellent mechanical strength as the substrate of the electrode material. Copper is plated on the surface of the carbon cloth using a chemical plating process to form a highly conductive substrate. Subsequently, the surface of the copper layer is partially etched and oxidized by alkali-assisted wet chemical oxidation to obtain a carbon cloth @ copper precursor covered with a cuprous oxide film. The film can not only improve the capacitance, but also act as a buffer layer to protect the substrate, protect the carbon cloth substrate from damage, and provide sufficient buffer space for the volume expansion that may occur during the charge and discharge process of the electrode material to obtain high specific capacitance and mechanical strength. Finally, a cobalt source is introduced into the reaction solution, a carbon cloth @ copper / cuprous oxide precursor is placed, and a hydrothermal reaction is carried out to obtain a multidimensional self-supporting carbon cloth @ cuprous oxide / basic copper carbonate / cobalt hydroxide composite material having a two-dimensional nanosheet / three-dimensional nanoblock hybrid structure, thereby significantly improving the electrochemical performance of the composite material.
[0044] 2. The preparation method of the present invention is simple and easy, and the prepared composite material has high specific capacitance and excellent cycle stability when used for supercapacitor electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 are scanning electron microscope images at different sizes, wherein the carbon cloth prepared in Example 1 is as follows Figure 1 A, 1B; Carbon cloth prepared in Example 1 @ copper such as Figure 1 C, 1D; Carbon cloth @ copper / cuprous oxide prepared in Example 1 Figure 1 E, 1F; Example 1 prepared carbon cloth @ cuprous oxide / basic copper carbonate / cobalt hydroxide composite material such as Figure 1 G, 1H;
[0046] Figure 2 This is an X-ray photoelectron spectrum of the carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material prepared in Example 1;
[0047] Figure 3 The cyclic voltammetry curves of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material prepared in Example 1 at different scan rates;
[0048] Figure 4 The carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material prepared in Example 1 was scanned at a rate of 100 mV s -1 Capacitance control and diffusion control ratio diagram when ;
[0049] Figure 5 is the normalized contribution rate of capacitance control and diffusion control to the total capacity of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material prepared in Example 1 at different scanning rates;
[0050] Figure 6 The constant current charge-discharge curves of the carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material prepared in Example 1 at different current densities;
[0051] Figure 7 1 is a cycle stability diagram and a coulomb efficiency diagram of the carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material prepared in Example 1;
[0052] Figure 8 The carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material prepared in Example 1, the carbon cloth prepared in Comparative Example 1, the carbon cloth@cobalt hydroxide prepared in Comparative Example 2, and the carbon cloth@copper / cuprous oxide prepared in Comparative Example 3 were scanned at a rate of 100 mV s -1 Cyclic voltammetry curves when
[0053] Fig. 9 The carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material prepared in Example 1, the carbon cloth@cobalt hydroxide prepared in Comparative Example 2, and the carbon cloth@copper / cuprous oxide prepared in Comparative Example 3 were subjected to 0.5 mA cm -2Constant current charge and discharge curves at a current density of;
[0054] Fig.10 X-ray powder diffraction patterns of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material prepared in Example 1, the carbon cloth@cobalt hydroxide prepared in Comparative Example 2, and the carbon cloth@copper / cuprous oxide prepared in Comparative Example 3;
[0055] Fig.11 Electrochemical AC impedance diagrams of the carbon cloth @ cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material prepared in Example 1, the carbon cloth @ cobalt hydroxide prepared in Comparative Example 2, and the carbon cloth @ copper / cuprous oxide prepared in Comparative Example 3. The insets are partial enlarged views of the high-frequency region and the balanced circuit diagram. DETAILED DESCRIPTION
[0056] The present invention will be further described below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the following embodiments.
[0057] Embodiment 1:
[0058] A method for preparing a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material for a high-performance flexible supercapacitor comprises the following steps:
[0059] (1) 1×1cm 2 The carbon cloth was ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water in turn, dried at 60°C for 8h, 10mL of concentrated nitric acid and 20mL of concentrated sulfuric acid were mixed as a mixed acid solution, the dried carbon was placed in the mixed acid solution, and magnetically stirred at room temperature for 10h, then the carbon cloth was taken out, ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water in turn, and dried at 60°C for 8h, then 0.24g of stannous chloride dihydrate was weighed and dissolved in 1.2M dilute hydrochloric acid as a sensitizing solution, the dried carbon was placed in the sensitizing solution, and magnetically stirred at room temperature for 25min, then the carbon cloth was taken out, repeatedly washed with ultrapure water, and dried at 60°C for 8h, finally, 0.08g of silver nitrate was weighed and dissolved in 0.134M dilute ammonia water as an activation solution, the dried carbon was placed in the activation solution, and magnetically stirred at room temperature for 15min, then the carbon cloth was taken out, repeatedly washed with ultrapure water, and dried at 60°C for 8h to obtain the pre-treated carbon cloth. Figure 1 middle Figure 1 (A) and 1(B) are scanning electron microscope images of carbon cloth at different sizes, and it can be seen that the surface of the carbon cloth is very smooth.
[0060] (2) After the carbon cloth was pretreated, in order to form a copper layer on the surface of the carbon cloth, a chemical plating solution was prepared: 0.7 g of copper sulfate pentahydrate was weighed and dissolved in 30 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution A; 2.28 g of potassium sodium tartrate, 0.45 g of sodium hydroxide and 0.21 g of sodium carbonate were weighed and dissolved in 40 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution B; the above-mentioned solutions A and B were mixed, and 2.65 mL of formaldehyde was measured and dissolved in the above solution to form a chemical plating solution, and the pH of the solution was adjusted to 12. The pretreated carbon cloth was placed in the chemical plating solution, and magnetic stirring was performed at 35°C for 150 min. Then the carbon cloth was taken out, the residual solution was rinsed off with ultrapure water, and it was dried at 60°C for 8 h to obtain a well-plated carbon cloth@copper substrate. Figure 1 (C) and (D) are scanning electron microscope images of carbon cloth@copper at different sizes. It can be seen that the carbon cloth is evenly and densely covered by the deposited copper, and the copper layer is composed of irregular spherical particles.
[0061] (3) Weigh 3 g of sodium hydroxide and 0.68 g of ammonium persulfate and dissolve them in 30 mL of ultrapure water. After ultrasonic treatment until the solution is clear and transparent, immerse the carbon cloth@copper substrate obtained in step (2) into the solution, and in-situ etch and oxidize for 15 min. Then take out the carbon cloth, rinse it repeatedly with ultrapure water, place the cleaned carbon cloth in a muffle furnace, and calcine it at 180° C. for 3 h to obtain a carbon cloth@copper / cuprous oxide precursor. Figure 1 (E) and (F) are scanning electron microscope images of carbon cloth@copper / cuprous oxide at different sizes. It can be seen that the cuprous oxide nanostructure on the surface of the copper layer appears as a thin film, and the morphology and arrangement of the copper layer inside the coating can be well preserved.
[0062] (4) Weigh 1.82 g of cobalt nitrate hexahydrate and 2.73 g of urea and dissolve them in 25 mL of ultrapure water. After ultrasonic treatment until the solution becomes clear and transparent, transfer it to a 50 mL high-pressure reactor, put the carbon cloth @ copper / cuprous oxide precursor obtained in step (3) into it, and perform a hydrothermal reaction at 120° C. for 12 h. The product is repeatedly rinsed with ultrapure water and dried at 60° C. for 12 h to obtain a carbon cloth @ cuprous oxide / basic copper carbonate / cobalt hydroxide composite material. Figure 1 (G) and (H) are scanning electron microscope images of carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide. It can be seen that during the hydrothermal process, the self-stacked three-dimensional basic copper carbonate nanoblocks can be well filled and coated by pine needle-shaped two-dimensional cobalt hydroxide nanosheets. This dense structure effectively increases the active sites of the Faraday redox reaction and can accelerate the transmission of ions and electrons in the electrolyte.
[0063] like Figure 2 This is the X-ray photoelectron spectrum of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material. It can be seen that carbon, oxygen, copper and cobalt elements exist in the composite material.
[0064] Embodiment 2:
[0065] A method for preparing a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material for a high-performance flexible supercapacitor comprises the following steps:
[0066] (1) 1×1cm 2 The carbon cloth was ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water in turn, dried at 60°C for 8h, 10mL of concentrated nitric acid and 20mL of concentrated sulfuric acid were mixed as a mixed acid solution, the dried carbon was placed in the mixed acid solution, and magnetically stirred at room temperature for 8h, then the carbon cloth was taken out, ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water in turn, and dried at 100°C for 5h, then 0.4g of stannous chloride dihydrate was weighed and dissolved in 1.2M dilute hydrochloric acid as a sensitizing solution, the dried carbon was placed in the sensitizing solution, and magnetically stirred for 20min at room temperature, then the carbon cloth was taken out, repeatedly washed with ultrapure water, and dried at 80°C for 9h, finally, 0.05g of silver nitrate was weighed and dissolved in 0.134M dilute ammonia water as an activation solution, the dried carbon was placed in the activation solution, magnetically stirred for 10min at room temperature, then the carbon cloth was taken out, repeatedly washed with ultrapure water, and dried at 70°C for 8h to obtain the pre-treated carbon cloth.
[0067] (2) After the carbon cloth was pretreated, in order to form a copper layer on the surface of the carbon cloth, a chemical plating solution was prepared: 0.5 g of copper sulfate pentahydrate was weighed and dissolved in 22 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution A; 3.5 g of potassium sodium tartrate, 0.8 g of sodium hydroxide and 0.4 g of sodium carbonate were weighed and dissolved in 36 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution B; the above-mentioned solutions A and B were mixed, and 4 mL of formaldehyde was measured and dissolved in the above solution to form a chemical plating solution; the pH of the solution was adjusted to 12, and the pretreated carbon cloth was placed in the chemical plating solution, and magnetic stirring was carried out at 30°C for 90 min. Then the carbon cloth was taken out, the residual solution was rinsed off with ultrapure water, and it was dried at 50°C for 9 h to obtain a well-plated carbon cloth@copper substrate.
[0068] (3) Weigh 5 g of sodium hydroxide and 0.5 g of ammonium persulfate and dissolve them in 40 mL of ultrapure water. After ultrasonic treatment until the solution is clear and transparent, immerse the carbon cloth @ copper substrate obtained in step (2) in the solution, and perform in-situ etching and oxidation for 10 min. Then take out the carbon cloth, rinse it repeatedly with ultrapure water, place the cleaned carbon cloth in a muffle furnace, and calcine it at 190 ° C for 3 h to obtain a carbon cloth @ copper / cuprous oxide precursor.
[0069] (4) Weigh 1 g of cobalt nitrate hexahydrate and 2 g of urea and dissolve them in 25 mL of ultrapure water. After ultrasonic treatment until the solution becomes clear and transparent, transfer it to a 50 mL high-pressure reactor and place the carbon cloth @ copper / cuprous oxide precursor obtained in step (3) into it. Perform a hydrothermal reaction at 130° C. for 10 h. The product is repeatedly rinsed with ultrapure water and dried at 70° C. for 12 h to obtain a carbon cloth @ cuprous oxide / basic copper carbonate / cobalt hydroxide composite material-1.
[0070] Embodiment three:
[0071] A method for preparing a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material for a high-performance flexible supercapacitor comprises the following steps:
[0072] (1) 1×1cm 2 The carbon cloth was ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water in turn, dried at 60°C for 8h, 10mL of concentrated nitric acid and 20mL of concentrated sulfuric acid were mixed as a mixed acid solution, the dried carbon was placed in the mixed acid solution, and magnetically stirred at room temperature for 12h, then the carbon cloth was taken out, ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water in turn, and dried at 100°C for 5h, then 0.3g of stannous chloride dihydrate was weighed and dissolved in 1.2M dilute hydrochloric acid as a sensitizing solution, the dried carbon was placed in the sensitizing solution, and magnetically stirred at room temperature for 30min, then the carbon cloth was taken out, repeatedly washed with ultrapure water, and dried at 80°C for 9h, finally, 0.1g of silver nitrate was weighed and dissolved in 0.134M dilute ammonia water as an activation solution, the dried carbon was placed in the activation solution, magnetically stirred at room temperature for 20min, then the carbon cloth was taken out, repeatedly washed with ultrapure water, and dried at 60°C for 8h to obtain the pre-treated carbon cloth.
[0073] (2) After the carbon cloth was pretreated, in order to form a copper layer on the surface of the carbon cloth, a chemical plating solution was prepared: 1.5 g of copper sulfate pentahydrate was weighed and dissolved in 30 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution A; 5 g of potassium sodium tartrate, 1 g of sodium hydroxide and 0.5 g of sodium carbonate were weighed and dissolved in 50 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution B; the above-mentioned solutions A and B were mixed, and 6 mL of formaldehyde was measured and dissolved in the above solution to form a chemical plating solution; the pH of the solution was adjusted to 12, and the pretreated carbon cloth was placed in the chemical plating solution, and magnetic stirring was carried out at 40°C for 180 min. Then, the carbon cloth was taken out, the residual solution was rinsed off with ultrapure water, and it was dried at 100°C for 5 h to obtain a well-plated carbon cloth@copper substrate.
[0074] (3) Weigh 6 g of sodium hydroxide and 1.5 g of ammonium persulfate and dissolve them in 60 mL of ultrapure water. After ultrasonic treatment until the solution becomes clear and transparent, immerse the carbon cloth@copper substrate obtained in step (2) into the solution, and perform in-situ etching and oxidation for 20 min. Then, take out the carbon cloth, rinse it repeatedly with ultrapure water, place the cleaned carbon cloth in a muffle furnace, and calcine it at 200 ° C for 3 h to obtain a carbon cloth@copper / cuprous oxide precursor.
[0075] (4) Weigh 2 g of cobalt nitrate hexahydrate and 3 g of urea and dissolve them in 25 mL of ultrapure water. After ultrasonic treatment until the solution becomes clear and transparent, transfer it to a 50 mL high-pressure reactor and put the carbon cloth @ copper / cuprous oxide precursor obtained in step (3) into it. Perform a hydrothermal reaction at 140° C. for 11 h. The product is repeatedly rinsed with ultrapure water and dried at 90° C. for 11 h to obtain a carbon cloth @ cuprous oxide / basic copper carbonate / cobalt hydroxide composite material-2.
[0076] Embodiment 4:
[0077] The obtained carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material was used as the working electrode, the saturated calomel electrode was used as the reference electrode, the platinum sheet electrode was used as the counter electrode, and 2M KOH was used as the electrolyte. The carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material was subjected to cyclic voltammetry test and constant current charge and discharge test using an electrochemical workstation.
[0078] like Figure 3 The cyclic voltammetry curves of carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite materials at different scanning rates. As the scanning rate increases, the closed area of the curve gradually increases, but the shape remains unchanged, indicating that the composite material has good reversibility and rate performance.
[0079] like Figure 4 The carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material was scanned at a rate of 100 mV s -1 Figure 5. Capacitance control and diffusion control ratio diagram of the reaction. The shaded part is the capacitance control process. According to formula (a), 89.46% of the total charge storage of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material is attributed to the capacitance control process.
[0080] i p (V) = k1v + k2v 1 / 2 (a)
[0081]
[0082] In formula (a), i p (V) represents the response current at a specific potential, v represents the scan rate, and k1 and k2 represent the capacitance control and diffusion control coefficients, respectively.
[0083] In formula (b), C s (mF cm -2 ) represents specific capacitance, I (mA) represents current, Δt (s) represents discharge time, S (cm 2 ) represents the effective area of the electroactive material and ΔV(V) represents the potential window.
[0084] like Figure 5 is the normalized contribution rate of capacitance control and diffusion control to the total capacity of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material at different scanning rates. As the scanning rate increases, the contribution rate of the capacitance control process to the total charge storage gradually increases.
[0085] like Figure 6 These are the constant current charge and discharge curves of carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composites at different current densities. All curves show an irregular triangular shape that is nearly symmetrical and nonlinear, indicating that the electrode material has the characteristics of both pseudocapacitance and double-layer capacitance.
[0086] like Figure 7 The cycle stability diagram and coulomb efficiency diagram of the carbon cloth @ cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material. After 1500 cycles of charge and discharge, the capacitance retention rate can still reach 100.3%, indicating that the electrode material has excellent cycle stability. At the same time, the coulomb efficiency of the carbon cloth @ cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material is almost maintained at 100%, which further proves that the electrode material has excellent electrochemical reversibility. Its good cycle stability and coulomb efficiency are mainly attributed to the hybrid structure of the two-dimensional nanosheets and three-dimensional nanoblocks of the electrode material, which provides a large specific surface area and a stable mesoporous structure, effectively inhibiting the expansion and deformation of the structure that may occur during the cycle.
[0087] Comparative Example 1:
[0088] The acidification of carbon cloth includes the following steps:
[0089] (1) Cut the carbon cloth into 1×1cm pieces 2 After size reduction, the carbon cloth was ultrasonically cleaned with ultrapure water, anhydrous ethanol and ultrapure water for 15 min in sequence, and then the cleaned carbon cloth was vacuum dried at 60 °C for 8 h.
[0090] (2) Measure 10 mL of concentrated nitric acid in a beaker, and then slowly add 20 mL of concentrated sulfuric acid into the beaker. At room temperature, stir magnetically to mix the two concentrated acids evenly. Place the carbon cloth obtained in step (1) in a beaker containing concentrated acid, stir magnetically for 10 hours at room temperature, take out the acidified carbon cloth and wash it repeatedly with ultrapure water, and vacuum dry it at 60°C for 8 hours. Use the activated carbon cloth as the working electrode, the saturated calomel electrode as the reference electrode, the platinum electrode as the counter electrode, and 2M KOH as the electrolyte, and perform cyclic voltammetry test on the activated carbon cloth using an electrochemical workstation. According to Figure 8 The carbon cloth was scanned at a rate of 100 mV s -1 From the cyclic voltammetry curve, it can be seen that the contribution of carbon cloth to the contrast capacitance is negligible.
[0091] Comparative Example 2:
[0092] Growing cobalt hydroxide on carbon cloth includes the following steps:
[0093] After the carbon cloth is acidified with mixed acid, 1.82g of cobalt nitrate hexahydrate and 2.73g of urea are weighed and dissolved in 25mL of ultrapure water. After ultrasonication until the solution is clear and transparent, the acidified carbon cloth is placed in the solution and transferred to a 50mL high-pressure reactor. A hydrothermal reaction is carried out at 120°C for 12h. The product is repeatedly rinsed with ultrapure water and dried at 60°C for 12h to obtain a carbon cloth with cobalt hydroxide grown on it. The carbon cloth@cobalt hydroxide is used as the working electrode, the saturated calomel electrode is used as the reference electrode, the platinum sheet electrode is used as the counter electrode, and 2M KOH is used as the electrolyte. The carbon cloth@cobalt hydroxide is subjected to cyclic voltammetry test and constant current charge and discharge test by an electrochemical workstation. According to Fig. 9 The constant current charge and discharge test diagram of carbon cloth @ cobalt hydroxide. The constant current charge and discharge test diagram of carbon cloth @ cobalt hydroxide can be calculated by formula (b) at a current density of 0.5 mA cm -2 When the specific capacitance is 374.75mF cm -2 .
[0094] Comparative Example 3:
[0095] Growing cuprous oxide on the surface of carbon cloth@copper includes the following steps:
[0096] (1) After the carbon cloth was pretreated, in order to form a copper layer on the surface of the carbon cloth, a chemical plating solution was prepared: 0.7 g of copper sulfate pentahydrate was weighed and dissolved in 20 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution A; 2.28 g of potassium sodium tartrate, 0.45 g of sodium hydroxide and 0.21 g of sodium carbonate were weighed and dissolved in 20 mL of ultrapure water, and the solution was sonicated until it became clear and transparent to form a solution B; the above two solutions A and B were mixed, and 2.65 mL of formaldehyde was measured and dissolved in the above solution to form a chemical plating solution, and the pH of the solution was adjusted to 12, and the pretreated carbon cloth was placed in the chemical plating solution, and magnetic stirring was performed at 35°C for 150 min, and then the carbon cloth was taken out, the residual solution was rinsed off with ultrapure water, and it was dried at 60°C for 8 h to obtain a well-plated carbon cloth@copper substrate.
[0097] (2) Weigh 3g of sodium hydroxide and 0.68g of ammonium persulfate and dissolve them in 30mL of ultrapure water. After ultrasonication until the solution becomes clear and transparent, immerse the carbon cloth @ copper substrate obtained in step (2) into the solution, and perform in-situ etching and oxidation for 15 minutes. Then take out the carbon cloth, rinse it repeatedly with ultrapure water, place the cleaned carbon cloth in a muffle furnace, and calcine it at 120°C for 3h to obtain a carbon cloth @ copper / cuprous oxide precursor. Use the carbon cloth @ copper / cuprous oxide as the working electrode, the saturated calomel electrode as the reference electrode, the platinum sheet electrode as the counter electrode, and 2M KOH as the electrolyte. Perform cyclic voltammetry and constant current charge and discharge tests on the carbon cloth @ copper / cuprous oxide using an electrochemical workstation. According to Fig. 9 The constant current charge and discharge test diagram of carbon cloth @ copper / cuprous oxide. The constant current charge and discharge test diagram of carbon cloth @ copper / cuprous oxide at a current density of 0.5 mA cm can be calculated by formula (b). -2 When the specific capacitance is 77.81mF cm -2 .
[0098] like Figure 8 The carbon cloth obtained in Comparative Example 1, the carbon cloth@cobalt hydroxide obtained in Comparative Example 2, the carbon cloth@copper / cuprous oxide obtained in Comparative Example 3, and the carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material obtained in Example 1 were tested at 100 mV s -1 Cyclic voltammetry curves at a scan rate of . It can be seen that the closed curve area of the carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material is much larger than that of other electrode materials. This may be due to the close contact between the three-dimensional basic copper carbonate nanoblocks and the two-dimensional cobalt hydroxide nanosheets in the hybrid structure, forming a highly conductive network that effectively improves the specific capacitance of the material. Among them, the closed curve area of the carbon cloth is very small in comparison, and its contribution to the specific capacitance of the electrode material can be ignored.
[0099] like Fig. 9The carbon cloth@cobalt hydroxide obtained in Comparative Example 2, the carbon cloth@copper / cuprous oxide obtained in Comparative Example 3, and the carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material obtained in Example 1 were subjected to 0.5 mA cm -2 The constant current charge-discharge curves at a current density of 0.5 mA cm-1 show that the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material has the longest charge-discharge time, indicating that its specific capacitance is the largest. According to formula (b), the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material has a constant current charge-discharge time of 0.5 mA cm-1. -2 The specific capacitance can reach 1016.25mF cm -2 ;according to Figure 8 The constant current charge and discharge test diagram of carbon cloth @ copper / cuprous oxide. The constant current charge and discharge test diagram of carbon cloth @ copper / cuprous oxide at a current density of 0.5 mA cm can be calculated by formula (b). -2 When the specific capacitance is 77.81mF cm -2 In addition, relatively symmetrical charge-discharge platforms were observed in the potential ranges of 0.0-0.2 V and 0.3-0.4 V, which was due to the redox reaction between cobalt ions and copper ions at the electrode-electrolyte interface. The results of the constant current charge-discharge curve analysis were consistent with those of the cyclic voltammetry curve analysis.
[0100] Fig.10The X-ray powder diffraction patterns of the carbon cloth @ cobalt hydroxide obtained in comparative example 2, the carbon cloth @ copper / cuprous oxide obtained in comparative example 3, and the carbon cloth @ cuprous oxide / basic copper carbonate / cobalt hydroxide composite material obtained in example 1 are shown. The diffraction peak at 2θ = 25.52° is a characteristic peak of carbon-based materials and exists in all samples. The diffraction peaks of carbon cloth @ cobalt hydroxide at 2θ = 32.47° and 38.66° are respectively attributed to the (100) and (002) crystal planes of cobalt hydroxide (JCPDS No. 30-0443), indicating the successful preparation of cobalt hydroxide. The three sharp diffraction peaks of carbon cloth @ copper / cuprous oxide at 2θ = 43.30°, 50.43° and 74.13° are respectively attributed to the (111), (200) and (220) crystal planes of metallic copper (JCPDS No. 04-0836), indicating that the copper layer has been successfully deposited on the carbon cloth. In addition, the diffraction peaks at 2θ=29.55°, 36.42°, 42.30° and 61.34° are respectively attributed to the (110), (111), (200) and (220) crystal planes of cuprous oxide (JCPDS No.05-0667), indicating that the copper hydroxide obtained by in-situ etching is successfully converted into cuprous oxide after thermal annealing. After the hydrothermal reaction, the diffraction peak of metallic copper disappears and is accompanied by diffraction peaks of basic copper carbonate (JCPDS No.72-1270) at 2θ=17.40°, 24.24°, 25.20°, 34.56°, 42.88°, 46.53°, 53.68° and 55.65°, which are attributed to (011), (-102), (111), (-113), (114), (015), (132) and (-106) crystal planes, respectively. In addition, diffraction peaks of cuprous oxide and cobalt hydroxide can also be observed in the composite material, indicating the successful synthesis of the composite material.
[0101] like Fig.11 These are the electrochemical AC impedance diagrams of carbon cloth@cobalt hydroxide, carbon cloth@copper / cuprous oxide, and carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composites. Combined with the local enlarged view of the high-frequency area in the inset, it can be seen that the semicircular arc diameter of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material in the high-frequency area, that is, the charge transfer resistance is smaller than that of carbon cloth@cobalt hydroxide and carbon cloth@copper / cuprous oxide, indicating that the charge transfer performance of the composite material has been significantly improved.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material, characterized in that: The carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material is a multi-dimensional self-supporting composite material with a hybrid structure of two-dimensional nanosheets and three-dimensional nanoblocks; Two-dimensional cobalt hydroxide nanosheets and three-dimensional basic copper carbonate nanoblocks grow simultaneously on the surface of the cuprous oxide buffer layer in no particular order, forming a composite material with a multi-dimensional hybrid structure.
2. A carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material as claimed in claim 1, characterized in that: The composite material is prepared by plating a copper layer on the surface of a carbon cloth to form a conductive substrate, covering the surface of the copper layer with a cuprous oxide film by alkali-assisted wet chemical oxidation, introducing cobalt hydroxide, and performing a hydrothermal reaction to obtain a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material.
3. A method for preparing a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) pre-treating the carbon cloth, placing it in a chemical plating solution, and performing chemical copper plating with magnetic stirring, taking out the carbon cloth, washing it with ultrapure water, and drying it to obtain a carbon cloth@copper conductive substrate; (2) weighing sodium hydroxide and ammonium persulfate and dissolving them in ultrapure water, ultrasonicating until the solution is clear and transparent, immersing the carbon cloth @ copper conductive substrate in the solution, performing in-situ etching and oxidation, taking out the carbon cloth, repeatedly rinsing it with ultrapure water, and calcining it in a muffle furnace to obtain a carbon cloth @ copper / cuprous oxide precursor; (3) Weighing cobalt nitrate hexahydrate and urea and dissolving them in ultrapure water, ultrasonicating until the solution is clear and transparent, transferring the solution to a high-pressure reactor, placing a carbon cloth@copper / cuprous oxide precursor, performing a hydrothermal reaction, repeatedly washing with ultrapure water, and drying to obtain a carbon cloth@cuprous oxide / basic copper carbonate / cobalt hydroxide composite material; The conditions of the hydrothermal reaction are: temperature 120-140° C., time 10-12 h.
4. The preparation method according to claim 3, characterized in that: The reaction conditions of the chemical copper plating are: temperature 30-40°C, time 90-180min; The drying conditions are: temperature 50-100°C, time 5-9h; The mass and volume ratio of the sodium hydroxide, ammonium persulfate and ultrapure water is 3-6 g: 0.5-1.5 g: 30-60 mL; The in-situ etching and oxidation conditions are: temperature 30-40° C., time 10-20 min; The calcination conditions are: temperature 180-200° C., time 3-4 hours.
5. The preparation method according to claim 3, characterized in that: The reaction conditions of the chemical copper plating are: temperature 35°C, time 150min; The in-situ etching and oxidation conditions are: temperature 35° C., time 15 min.
6. The preparation method according to claim 3, characterized in that: In step (3), the mass ratio of cobalt nitrate hexahydrate to urea is 1-2:2-3; The conditions of the hydrothermal reaction are: temperature 120°C, time 12h; The drying conditions are: temperature 50-100° C., time 10-12 h.
7. The preparation method according to claim 3, characterized in that: The specific steps of pre-treating the carbon cloth are: (A) The carbon cloth is cleaned with ultrapure water, anhydrous ethanol, and ultrapure water ultrasonically in sequence, and dried for later use; (B) Mixing concentrated nitric acid and concentrated sulfuric acid as a mixed acid solution, placing the dried carbon cloth in the mixed acid solution and subjecting it to magnetic stirring for acidification, taking out the carbon cloth, and ultrasonically cleaning it with ultrapure water, anhydrous ethanol, and ultrapure water in sequence, and drying it for later use; (C) weighing stannous chloride dihydrate and dissolving it in dilute hydrochloric acid as a sensitizing solution, placing the dried carbon cloth obtained in the above step (B) in the sensitizing solution and subjecting it to magnetic stirring for sensitization treatment, taking out the carbon cloth, repeatedly washing it with ultrapure water, and drying it for later use; (D) weighing silver nitrate and dissolving it in dilute ammonia water as an activation solution, placing the carbon cloth obtained in the above step (C) in the activation solution and subjecting it to magnetic stirring for activation treatment, taking out the carbon cloth, repeatedly washing it with ultrapure water, and drying it to obtain a pre-treated carbon cloth; The preparation method of the chemical plating solution is: (a) Weigh copper sulfate pentahydrate and dissolve it in ultrapure water, and sonicate until the solution becomes clear and transparent to form solution A; (b) Weighing potassium sodium tartrate, sodium hydroxide and sodium carbonate, dissolving them in ultrapure water, and sonicating until the solution becomes clear and transparent to prepare solution B; (c) Solution A and solution B are mixed, formaldehyde is added, and the pH is adjusted to 12 to obtain a chemical plating solution.
8. The preparation method according to claim 7, characterized in that: The volume ratio of the concentrated nitric acid to the concentrated sulfuric acid is 10:20; The mass and volume ratio of the stannous chloride dihydrate to the dilute hydrochloric acid is 0.2-0.4 g:10-14 mL, and the concentration of the dilute hydrochloric acid is 1.2 M; The mass-to-volume ratio of the silver nitrate to the dilute ammonia water is 0.05-0.1 g:10-14 mL, and the concentration of the dilute ammonia water is 0.134 M; The reaction time of the acidification treatment is 8 to 12 hours; The reaction time of the sensitization treatment is 20 to 30 minutes; The reaction time of the activation treatment is 10 to 20 minutes; The drying conditions are: temperature 50-100° C., time 5-9 h.
9. The preparation method according to claim 7, characterized in that: The reaction time of the acidification treatment is 10h; The reaction time of the sensitization treatment is 25 min; The reaction time of the activation treatment is 15 min.
10. The preparation method according to claim 7, characterized in that: The mass ratio of the copper sulfate pentahydrate, potassium sodium tartrate, sodium hydroxide and sodium carbonate is 0.5-1.5:2-5:0.4-1:0.2-0.5; The volume ratio of the formaldehyde, A solution and B solution is 2-6:22-34:36-60.
11. Use of the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material as claimed in claim 1 or 2 as a supercapacitor electrode material.
12. A working electrode in an electrochemical three-electrode system, characterized in that: It comprises the carbon cloth@cuprous oxide / basic cupric carbonate / cobalt hydroxide composite material as claimed in claim 1 or 2.
Citation Information
Patent Citations
Preparation method for different carbon fibers / cobalt hydroxide electrode and solid-liquid composite electrode system
CN103426649A
Porous CoAl bimetal hydroxide@carbon fabric composite electrode material and preparation method thereof
CN108666148A